Preparation for Marriage: Can. 1063, 2 and Pope Francis Proposal for Catechumenate for Marriage Preparation - Gonçalves López, Eduardo José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The preparation for the sacrament of marriage — before and after its celebration — always has been considered an important pastoral need, with a heavy spiritual meaning to the life of the couple as well as to the Christian community. Therefore, the Church has been taken steps toward a progressive conscience of the need for an evangelization process — kerygmatic and catechumenal — for the preparation of new families. This article offers a judicial — pastoral approximation for the wedding preparation, through the presentation of the Church’s legislation, from the doctrine of the Pius-Benedictine Code of 1917 to the current Canon Law of 1983. This presentation follows selected and important interventions from Pope Francis’ Magisterium regarding the need for adequate marriage preparation and the concrete proposal of a pre-marriage catechumenate as a much-needed answer to this pastoral challenge.